2007
DOI: 10.1038/sj.bjp.0707382
|View full text |Cite
|
Sign up to set email alerts
|

Kaurane diterpenes protect against apoptosis and inhibition of phagocytosis in activated macrophages

Abstract: Background and purpose: The kaurane diterpenes foliol and linearol are inhibitors of the activation of nuclear factor kB, a transcription factor involved in the inflammatory response. Effects of these diterpenes on apoptosis and phagocytosis have been analysed in cultured peritoneal macrophages and in the mouse macrophage cell line, RAW 264.7. Experimental approach: Macrophages were maintained in culture and activated with pro-inflammatory stimuli in the absence or presence of diterpenes. Apoptosis and the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…The only differences were the disappearance of a carboxylic acid group, an olefinic methyl group (CH 3 -16), and an olefinic proton (H-14) in compound 2 and the appearance of a new multiplet corresponding to oxygenated methylene protons at δ H 3.78 and 3.46. Inspection of HMQC and DEPT spectra of 2 confirmed the presence of three methyls, eight methylenes, two methines, and three quaternary carbons ( Table 1) 13 C, HMQC, and DEPT NMR spectroscopic inspection of the aglycon moiety of 3a confirmed the presence of four methyls, nine methylenes, three methines, and four quaternary carbons ( Table 1). Two of the methylene carbons were oxygenated at δ C 61.5 (δ H 4.55) and 72.7 (δ H 3.58/3.83), and on the basis of 2J and 3J correlations from the methyl protons at C-20 and C-16, respectively, observed in the HMBC spectrum, the methylene carbons at δ C 61.5 and 72.7 could be assigned to C-15 and C-19, in turn.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…The only differences were the disappearance of a carboxylic acid group, an olefinic methyl group (CH 3 -16), and an olefinic proton (H-14) in compound 2 and the appearance of a new multiplet corresponding to oxygenated methylene protons at δ H 3.78 and 3.46. Inspection of HMQC and DEPT spectra of 2 confirmed the presence of three methyls, eight methylenes, two methines, and three quaternary carbons ( Table 1) 13 C, HMQC, and DEPT NMR spectroscopic inspection of the aglycon moiety of 3a confirmed the presence of four methyls, nine methylenes, three methines, and four quaternary carbons ( Table 1). Two of the methylene carbons were oxygenated at δ C 61.5 (δ H 4.55) and 72.7 (δ H 3.58/3.83), and on the basis of 2J and 3J correlations from the methyl protons at C-20 and C-16, respectively, observed in the HMBC spectrum, the methylene carbons at δ C 61.5 and 72.7 could be assigned to C-15 and C-19, in turn.…”
supporting
confidence: 50%
“…12,13 For use in traditional medicine Crassocephalum tea is prepared from fresh plants (500 g plant material/L H 2 O) and consumed three times daily until pain subsides.…”
mentioning
confidence: 99%
“…The phagocytosis was assayed by detecting ingestion of E.coli fluorescent particles by macrophages [20]. Macrophages (2×10 5 cells/ml) were placed in 24-well culture plates and treated with different concentrations of BPs for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Well accepted that many plant-derived compounds possess analgesic and anti-inflammatory properties. Recent studies have shown that the labdane diterpene of the air-dried parts of Crassocephalum mannii has anti-inflammatory activity through its cyclooxygenase inhibitory activity (Heras et al, 2007;Liua et al, 2006;MohamedElamir et al, 2008). Although the potent activity of non-steroidal anti-inflammatory drugs is noteworthy, they have also many severe adverse effects.…”
Section: Introductionmentioning
confidence: 96%